A Low Prevalence and Complementary Nature of Traditional Medicine Use in Maternal Healthcare: Evidence from Cambodia Demographic and Health Survey 2021-22: Traditional Medicine Use in Cambodia - Sokha Yem; Kem Sokunthea; Tun Sreypeov (CV Media Inti Teknologi, 2026)
Background: Cambodia has achieved substantial gains in modern maternal healthcare coverage, yet nationally representative evidence on residual traditional birth attendant (TBA) use and home delivery, and whether these persist alongside or instead of modern care, remains limited. This study estimated the prevalence and correlates of TBA use and home delivery in Cambodia.Aims: This study estimated the prevalence, patterns, and correlates of TBA use and home delivery in maternal healthcare in Cambodia.Methods: We analyzed data on 6,968 women with a birth in the five years preceding the Cambodia Demographic and Health Survey (CDHS) 2021–22. TBA/home-delivery (TBA/HD) care was defined as antenatal care from a TBA, delivery assisted by a TBA, or home (non-facility) delivery. Weighted prevalence and survey-adjusted multivariable logistic regression identified correlates.Results: Overall prevalence of TBA/HD care was 1.25% (95% CI: 0.92–1.69%; 154/6,968 unweighted) and was markedly higher among rural than urban women, among women with no education than higher education, among the poorest than the richest wealth quintile, and among women with four or more children than one child (all p<0.001). In the fully adjusted model, the poorest quintile had over six times the odds of TBA/HD care versus the richest (aOR=6.82, 95% CI: 2.10–22.13), p=0.001), and women with one child had 69% lower odds versus those with four or more (aOR=0.31, 95% CI: 0.16–0.61). p=0.001). Residence and education were not independently significant after adjustment.Conclusion: TBA use and home delivery are uncommon in Cambodia and concentrated among the poorest and highest-parity women; wealth and parity, more than education or residence, distinguish residual TBA/HD care after adjustment. Findings support targeting the poorest women rather than population-wide campaigns.